1989
DOI: 10.1002/jlb.45.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Cytomegalovirus Infection on Functions and Arachidonic Acid Metabolism of Rat Peritoneal Macrophages

Abstract: An intraperitoneal (rat) cytomegalovirus (RCMV) infection in the rat caused an influx of mononuclear cells, which have been altered in functions and arachidonic acid (AA) metabolism. Phagocytosis has been increased considerably 3 days postinfection (p.i.), whereas the release of prostacyclin, thromboxane A2, 12-hydroxyheptadecatrienoic acid (HHT), 5-hydroxyeicosatetraenoic acid (5-HETE), and leukotriene B4 (LTB4) was inhibited for more than 80%. The release of superoxide anions and the chemiluminescence respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…By analyzing the absolute numbers of pMF isolated by peritoneal lavage at different time points after infection, we showed that 1 day after infection the number of pMF present in the PC is significantly increased, most likely as a result of recruitment of mononuclear cells into the peritoneum. This increase in pMF numbers in response to RCMV infection was previously reported by Engels et al who moreover showed that this influx of mononuclear cells was preceded by an influx of polymorphonuclear granulocytes (PMN), reaching maximum numbers already 2 h after infection (Engels et al, 1989). At 1 day after infection we also observed increased numbers of PMN's, but the vast majority of isolated cells at this time point consisted of macrophages as determined by specific immunohistochemistry.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By analyzing the absolute numbers of pMF isolated by peritoneal lavage at different time points after infection, we showed that 1 day after infection the number of pMF present in the PC is significantly increased, most likely as a result of recruitment of mononuclear cells into the peritoneum. This increase in pMF numbers in response to RCMV infection was previously reported by Engels et al who moreover showed that this influx of mononuclear cells was preceded by an influx of polymorphonuclear granulocytes (PMN), reaching maximum numbers already 2 h after infection (Engels et al, 1989). At 1 day after infection we also observed increased numbers of PMN's, but the vast majority of isolated cells at this time point consisted of macrophages as determined by specific immunohistochemistry.…”
Section: Discussionsupporting
confidence: 88%
“…At all time points analyzed we could detect infected pMF using immunohistochemical detection of RCMV IE-antigens, although the percentages were low (, 0.05%). This suggests that almost no reproductive infection occurs in pMF (Engels et al, 1989). This does not exclude the possibility that many cells have taken up virus, however, without subsequent viral replication (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…However, perhaps mCMV-HC leads to levels of vascular NAD(P)H oxidase-derived ROS that are sufficient to induce platelet, but not leukocyte, adhesion, or mCMV-HC activates other pathways that overcome any anti-inflammatory effect of gp91 phox deficiency or apocynin treatment. There are conflicting reports about the induction of ROS by CMV in leukocytes [3032], albeit these data were obtained during primary infection, and our data would suggest that if ROS are generated by leukocytes in response to mCMV-HC, NAD(P)H oxidase is not the primary source. The possibility remains that other oxidant-generating enzymes or dysregulation of antioxidant defenses in the vessel wall and/or circulating blood cells may mediate the venular inflammation in mCMV-HC mice.…”
Section: Discussionmentioning
confidence: 59%
“…Decreased O 2 ·− has been reported in CMV-infected macrophages [30] and neutrophils [31], whereas this virus has been show to elevate ROS generation in monocytes [32] and vascular smooth muscle cells [33]. Furthermore, responses differ between endothelial cells, in that human umbilical vein endothelial cells do not have altered ROS release upon CMV infection [34], but microvascular endothelial cells show enhanced intracellular oxidative stress under basal conditions, and exacerbated DMNQ-induced O 2 ·− generation [35].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro-studies indicate that CMV stimulates arachidonic acid metabolism [l] and that inhibitors of prostaglandin synthesis inhibit growth of CMV [21, 221. In one study, however, rat CMV infection was shown to decrease the number of arachidonic acid metabolites in peritoneal macrophages [6]. CMV immediate early proteins have been shown to transactivate the COX-2 gene, probably via NF-KB, and COX-2 has been reported to play an important role in the cell activation cascade induced by CMV, making the environment favorable for replication of the virus [21].…”
Section: Discussionmentioning
confidence: 99%